Research self-efficacy and attitude towards research evidence from students at University of Health Sciences, Cambodia - Aim Sothea
Background: Thesis completion was as low as 13% for medical students, 60% for dentistry and none for nursing students in the University of Health Sciences in Cambodia which causes concern for university management and anxiety for students themselves. This low academic performance may be attributed to student self-efficacy and interest. Moreover, students held negative views about research and fear and anxiety about statistics. We examined perceived research self-efficacy (i.e. confidence in executing successfully specific research activities) and attitude towards research (i.e. preferable tendency towards research) and their correlation. Findings from the study would serve as baseline and may help research instructors to adopt learning experiences to boost students? research self-efficacy and attitude towards research. Objective of the Study: The main objective of study was to determine the level of research self-efficacy and attitude towards research and the correlation between these two variables. Methodology: Cross-sectional survey was used for the present study. Anonymous self-administered 13-item Clinical Research Appraisal Inventory (CRAI) and 18-item Attitude towards Research (ATR) scale were distributed to 361 students in their final year of study in three academic programs: medicine, dentistry and nursing at University of Health Sciences. Data were entered in EpiData 3.1 and analyzed using Stata 11 SE. Appropriate statistical tests were used with significance level at α=0.05. Results: A total of 332 students participated in this study with the response rate of 92%. Overall, students reported moderate level of research self-efficacy with mean percentage score of 55.9% (sd=16.9%) and moderate positive attitude towards research with mean percentage score of 66.5% (sd=11.4%). Students perceived on research self-efficacy and attitude towards research significantly different across the three academic programs, and not based on their gender on variables of research self-efficacy and attitude towards research. Research self-efficacy was statistically and moderately positively linked to attitude towards research. Conclusion: Overall, students reported moderate level of research self-efficacy and moderate positive attitude towards research. There was a positive correlation between research self-efficacy and attitude towards research. Recommendation: There is a need to enhance their research self-efficacy and attitude towards research of University of Health Sciences in Cambodia. This can be done by improving instructional strategies and curricular design to help improve the completion of thesis/memoir writing up.